3D morphometric quantification of maxillae and defects for patients with unilateral cleft palate via deep learning‐based CBCT image auto‐segmentation. (25th March 2021) - Wang, Xiaoyu; Pastewait, Matthew; Wu, Tai‐Hsien; Lian, Chunfeng; Tejera, Beatriz; Lee, Yan‐Ting; Lin, Feng‐Chang; Wang, Li; Shen, Dinggang; Li, Song; Ko, Ching‐Chang
Abstract: Objective: This study aimed to quantify the 3D asymmetry of the maxilla in patients with unilateral cleft lip and palate (UCP) and investigate the defect factors responsible for the variability of the maxilla on the cleft side using a deep‐learning‐based CBCT image segmentation protocol. Setting and sample population: Cone beam computed tomography (CBCT) images of 60 patients with UCP were acquired. The samples in this study consisted of 39 males and 21 females, with a mean age of 11.52 years (SD = 3.27 years; range of 8‐18 years). Materials and methods: The deep‐learning‐based protocol was used to segment the maxilla and defect initially, followed by manual refinement. Paired t ‐tests were performed to characterize the maxillary asymmetry. A multiple linear regression was carried out to investigate the relationship between the defect parameters and those of the cleft side of the maxilla. Results: The cleft side of the maxilla demonstrated a significant decrease in maxillary volume and length as well as alveolar length, anterior width, posterior width, anterior height and posterior height. A significant increase in maxillary anterior width was demonstrated on the cleft side of the maxilla. There was a close relationship between the defect parameters and those of the cleft side of the maxilla. Conclusions: Based on the 3D volumetric segmentations, significant hypoplasia of the maxilla on the cleft side existed in the pyriform aperture and alveolar crest area near the defect. The defect structures appeared to contribute to the variability of the maxilla on the cleft side.